PART 2 An Experiment on the Box plot - M. Hussin, Mahmud (Journal of Economics and Administrative Sciences, 2007)
Abstract These experiments seek to investigate the effects of the fixed variations to the basic box plot on subjects’ judgments of the box lengths. The study consists of two experiments, were constructed as an extension to the experiments carried out previously by Hussin, M.M. (1989, 2006). Subjects were asked to judge what percentage the shorter represented of the longer length in pairs of box lengths and give an estimate of percentage, one being a standard plot and the other being of a different box length and also varying with respect to other elements such as, box width or whisker length. When he (1989) suggested in the future research points (1, 2), the changing length of the standard box plot effects on the subjects’ perception of the box length. However, both experiments were used the stander box length as the middle box length levels in the experiments. The results of these two experiments indicated that these variations effected the subjects’ perception of box length. we thought that the effect in the subjects perception of these variations it might be that the subjects were affected by the visual illusion effects as Cleveland et al (1987) accepted in their replies to the comments on their work, as a results of the interactions between box plot features as which effect the subjects ability to accurately judge box length and the effects differed between variations, both experiments were run in statistics department, Baghdad University.